2018
DOI: 10.1111/apt.14569
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery is associated with increased risk of new‐onset inflammatory bowel disease: case series and national database study

Abstract: New-onset IBD was significantly associated with a past history of bariatric surgery. This potential association needs to be confirmed in future prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…Current knowledge about the role of bariatric surgery in the development of de novo IBD is scarce. To date, 17 cases of ulcerative colitis (UC), 60 cases of CD and three cases of unclassified colonic IBD after gastrointestinal bariatric surgery have been reported in the literature, most of them with endoscopic and histological findings consistent with IBD .…”
Section: Development Of De Novo Ibd After Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Current knowledge about the role of bariatric surgery in the development of de novo IBD is scarce. To date, 17 cases of ulcerative colitis (UC), 60 cases of CD and three cases of unclassified colonic IBD after gastrointestinal bariatric surgery have been reported in the literature, most of them with endoscopic and histological findings consistent with IBD .…”
Section: Development Of De Novo Ibd After Bariatric Surgerymentioning
confidence: 99%
“…recently published the results of a case‐control study using a US national database from Source Healthcare Analytics LLC. After adjusting for confounders, a past history of bariatric surgery was associated with and increased risk of new‐onset IBD (OR 1.93, 95% CI 1.34‐2.79) …”
Section: Development Of De Novo Ibd After Bariatric Surgerymentioning
confidence: 99%
“…Ungaro et al have reported one of the largest case series of patients with de novo IBD following bariatric surgery. In an analysis of 8980 cases following bariatric surgery, they described 15 cases of IBD, with the majority being female patients with Crohn's disease (CD) who underwent Roux‐en‐Y surgery.…”
mentioning
confidence: 99%
“…Alukaidey and Heerasing regarding our recent paper in Alimentary Pharmacology & Therapeutics . We agree that we cannot infer causality based on the current evidence from our study and a recent similar paper from the group at Mayo Clinic . Rather, as we note in our manuscript, this association needs to be explored further in prospective studies and additional studies on the physiologic changes that occur following bariatric surgery (microbiome, metabolic, etc.)…”
mentioning
confidence: 56%